IMPROVEMENT OF STUDENTS ABILITY IN USING TENSES THROUGH TEXT AND DRILLS METHOD OF STUDENTS ENGLISH EDUCATION DEPARTMENT OF LANCANG KUNING UNIVERISTY PEKANBARU - Indah MUZDALIFAH (Universitas Pahlawan Tuanku Tambusai, 2016)
ABSTRACT: The aim of this research is to describe the influence of Text and Drill Method in improving the students ability in learning tenses. Based on preliminary observation in previous semester, the students English department was weak in applying tenses in sentence. Thus, this research was trying to find the whether the method text and drill can improve their ability in learning tenses or not as well as to find out the factors that influence its improvement. The type of this research was using Classroom Action Research method. The technique of collecting and analyzing the data was using test, observation, interview and field note. The result of this research is there was significant improving of the students ability in learning tenses by using text and drill method. Besides, the factors that influence their improving is the learning strategy that the lecture gave during the process of learning, the material that was used, and the media that support in teaching learning the tense.